Solar powered street lamp / Ahmad Haikal Abdul Hanan, Mohamad Firdaus Ishak and Muhammad Syafiq Mansor - Abdul Hanan, Ahmad Haikal; Ishak, Mohamad Firdaus; Mansor, Muhammad Syafiq (2013)
Electrical bill nowadays are increase, so the solar powered street lamp is used to reduce cost of electrical bill. This project is to contribute to UiTM where it will reduce the cost of the electrical bill and can become of the symbolic to UiTM student which using their own project at their own campus. Solar powered street lamp is one of the examples of using solar where it is renewable energy so it will not harm the environment. In this project it conduct 3 phase of the circuit where it contain solar charging, LDR, and inverter circuit. This is the simple circuit where it will reduce the cost in produce circuit. Besides that, it only need low maintenance compared to the conventional street lamp.